The Effectiveness of Problem-Based Learning Model in Developing Critical Thinking Skills on the “Youth Pledge” Topic Within the Framework of “Bhinneka Tunggal Ika” - Nurul Azizah; Elly Hasan Sadeli; Ratna Kartika Wati (Proceedings Series on Social Sciences & Humanities, 2023)
This research aims to determine the effectiveness of the Problem-Based Learning (PBL) model in developing critical thinking skills on the "Youth Pledge." The method employed in this study is a quasi-experiment with a non- equivalent control group design. The sample consists of Grade VIII A as the experimental group (n=30) and Grade VIII C as the control group (n=30). The data collection techniques include questionnaires,  observations, and documentation analysis, which were analyzed using alternative paired sample test and independent sample t-test with results of 0.000 0.05, indicating that the Problem-Based Learning model effectively cultivates critical thinking skills among students. This is supported by the results of the n-gain present test, which yielded a score of 61.81% for the experimental group and 34.31% for the control group. The effect size test yielded a value of 2.61, falling into the category of high influence.